2011
DOI: 10.1038/nchem.981
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-mediated intracellular chemistry

Abstract: Many important intracellular biochemical reactions are modulated by transition metals, typically in the form of metalloproteins. The ability to carry out selective transformations inside a cell would allow researchers to manipulate or interrogate innumerable biological processes. Here, we show that palladium nanoparticles trapped within polystyrene microspheres can enter cells and mediate a variety of Pd(0)-catalysed reactions, such as allylcarbamate cleavage and Suzuki-Miyaura cross-coupling. The work provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
433
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 467 publications
(441 citation statements)
references
References 31 publications
(38 reference statements)
5
433
0
3
Order By: Relevance
“…It is proposed that the high cytotoxicity of Pd@W.tea NPs to the cancer cell line is due to the presence of Pd, which interacts physicochemically with the functional groups of cellular proteins, nitrogen bases, and phosphate groups of the DNA, 36 thus causing cell death. Moreover, previous studies showed that Pd causes production of free radical, 37 lactate dehydrogenase leakage, 15 and cell-cycle disturbances 38 that could be among mechanisms of the anticancer effects of Pd@W.tea NPs.…”
Section: In Vitro Cytotoxicitymentioning
confidence: 99%
“…It is proposed that the high cytotoxicity of Pd@W.tea NPs to the cancer cell line is due to the presence of Pd, which interacts physicochemically with the functional groups of cellular proteins, nitrogen bases, and phosphate groups of the DNA, 36 thus causing cell death. Moreover, previous studies showed that Pd causes production of free radical, 37 lactate dehydrogenase leakage, 15 and cell-cycle disturbances 38 that could be among mechanisms of the anticancer effects of Pd@W.tea NPs.…”
Section: In Vitro Cytotoxicitymentioning
confidence: 99%
“…The latest advances in bioorthogonal chemistry1 demonstrate how organometallic compounds and inorganic materials are capable of catalyzing the activation of profluorescent substrates and prodrugs with remarkable efficiency in biological environments 2, 3, 4, 5, 6, 7, 8, 9, 10. These selective catalysts carry out non‐natural reactions dodging the interference of biological molecules, in some cases with endogenous cellular components as co‐reactants 3, 9…”
mentioning
confidence: 99%
“…钯催化的碳-碳偶 联反应对现代合成化学具有革命性的意义, 其对有机化 学的贡献受到了广泛的关注和认同, 并最终于 2010 年 获得了诺贝尔化学奖 [12] . 部分钯催化的偶联反应, 尤其 像 Suzuki-Miyaura 交叉偶联反应, 能够兼容中性、 水相、 室温等和细胞环境相似的温和条件 [13] . 更为重要的是 对于目前已知的生命体系中还未发现钯离子的存在和 作用 [14] , 这使得钯成为了一种非常吸引人的生物正交 反应的催化剂.…”
Section: 生物正交反应unclassified